2017
DOI: 10.1016/j.molcel.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol-Induced Nur77 Interaction with TRAF2 Alleviates Inflammation by Promoting Mitochondrial Ubiquitination and Autophagy

Abstract: SUMMARY Mitochondria play an integral role in cell death, autophagy, immunity, and inflammation. We previously showed that Nur77, an orphan nuclear receptor, induces apoptosis by targeting mitochondria. Here, we report that celastrol, a potent anti-inflammatory pentacyclic triterpene, binds Nur77 to inhibit inflammation and induce autophagy in a Nur77-dependent manner. Celastrol promotes Nur77 translocation from the nucleus to mitochondria, where it interacts with tumor necrosis factor receptor-associated fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
203
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(211 citation statements)
references
References 73 publications
8
203
0
Order By: Relevance
“…A recent study revealed an anti-inflammatory mechanism of mitophagy in which celastrol promotes NR4A1 (nuclear receptor subfamily 4 group A member 1) translocation from the nucleus to mitochondria, where it is ubiquitinated by TRAF2 (TNF receptor associated factor 2). Ubiquitinated NR4A1 then interacts with SQSTM1, leading to mitophagy and the alleviation of inflammation [72]. Consistent with this finding, SESN2 (sestrin 2), a stress-inducible protein, suppresses prolonged NLRP3 inflammasome activation by clearing damaged mitochondria via the induction of mitophagy in macrophages [73].…”
Section: Viruses Subvert Mitophagy To Attenuate Inflammation Activationmentioning
confidence: 67%
“…A recent study revealed an anti-inflammatory mechanism of mitophagy in which celastrol promotes NR4A1 (nuclear receptor subfamily 4 group A member 1) translocation from the nucleus to mitochondria, where it is ubiquitinated by TRAF2 (TNF receptor associated factor 2). Ubiquitinated NR4A1 then interacts with SQSTM1, leading to mitophagy and the alleviation of inflammation [72]. Consistent with this finding, SESN2 (sestrin 2), a stress-inducible protein, suppresses prolonged NLRP3 inflammasome activation by clearing damaged mitochondria via the induction of mitophagy in macrophages [73].…”
Section: Viruses Subvert Mitophagy To Attenuate Inflammation Activationmentioning
confidence: 67%
“…Clearly NR4A1 can have different ubiquitination sites in different cellular contexts. For example, during inflammation, ubiquitinated NR4A1 is not send to proteasomal degradation but functions as a label of damaged mitochondria, interacting with the autophgic receptor p62/SQSTM1 for their engulfment and elimination by mitophagy (44). Further experiments will be needed to understand the combinations of PTMs that regulate NR4A1 half-life, intracellular localization and interactors, which render specific functions in different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Celastrol was shown to protect against obesity and metabolic dysfunction through activation of the transcription factor HSF1, which regulates metabolic programs in adipose tissue and muscle [8]. Further studies showed that celastrol binds specifically to the nuclear receptor Nur77, which may confer the leptinsensitizing effect by regulating HFD-induced hypothalamic inflammation [9]. In addition, celastrol has been found to have a strong protective effect in several other human conditions [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%